2015
DOI: 10.1111/polp.12128
|View full text |Cite
|
Sign up to set email alerts
|

Venue Effects: How State Policy Source Influences Policy Support

Abstract: Does receiving information about a policy's source shape individual support for the policy? Is the public more supportive of policies issued by courts, legislatures, or citizens voting on a ballot initiative? Using a survey experiment, we find strong evidence that learning about a policy's source can affect support for the policy. Specifically, we find that state‐level policy sources influence both the degree and direction of influence on policy support. In general, when informed about a policy's source, surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…The finding is supported by the earlier field experiments of Olken (2010), who concludes that ''direct participation in political decision making can substantially increase satisfaction and legitimacy.'' Similarly, Gash and Murakami (2015) find that control over the decision increases acceptance of the decision: ''individuals are more likely to agree with, and less willing to work against, policies that have been produced by their fellow citizens,'' moderated by partisan affiliation. We seek to qualify these results in a real-world election context at the level of a German federal state.…”
Section: Research Questionmentioning
confidence: 95%
“…The finding is supported by the earlier field experiments of Olken (2010), who concludes that ''direct participation in political decision making can substantially increase satisfaction and legitimacy.'' Similarly, Gash and Murakami (2015) find that control over the decision increases acceptance of the decision: ''individuals are more likely to agree with, and less willing to work against, policies that have been produced by their fellow citizens,'' moderated by partisan affiliation. We seek to qualify these results in a real-world election context at the level of a German federal state.…”
Section: Research Questionmentioning
confidence: 95%
“…OECD, 2020) and in empirical studies that test these theoretical claims. Most experimental studies found that citizen involvement in decision-making has positive effects on attitudes related to political support, such as external efficacy, legitimacy perceptions, or trust (Boulianne, 2018;Esaiasson et al, 2012Esaiasson et al, , 2019Grönlund et al, 2010;Herian et al, 2012;Sulkin & Simon, 2001;Terwel et al, 2010;Ulbig, 2008;Werner & Marien, 2020), although some studies did not find such effects (Gash & Murakami, 2009;Morrell, 1999). Observational studies have yielded mixed findings with some finding positive (but small) associations between referendums and legitimacy perceptions (Bauer & Fatke, 2014;Jäske, 2018;Marien & Kern, 2018).…”
Section: How Engagement With Citizen Lobby Can Potentially Build Poli...mentioning
confidence: 99%
“…Finally, I report evidence from a survey experiment which was designed to test important microlevel predictions of my theory, namely, that the extent to which self-determination referendums are seen as fair and their results accepted by members of both the minority and the majority group depends on whether or not they are mutually agreed. The design of the experiment builds on existing studies from the procedural fairness literature that have used randomized vignettes to test the legitimacy-generating potential of different political decision-making mechanisms, such as referendums (Esaiasson et al, 2012;Gash and Murakami, 2015;Towfigh et al, 2016;Esaiasson et al, 2019;Werner and Marien, 2022). As previously mentioned, this literature has tended to find that decision-making by referendum generates comparatively high fairness perceptions and decision acceptance.…”
Section: Survey Experimentsmentioning
confidence: 99%
“…However, in recent years, the empirical evidence in favor of the superior ability of referendums to generate fairness perceptions and decision acceptance has started to mount. For example, survey experimental evidence from several Western countries including Germany, the Netherlands, Sweden, and the USA suggests that citizens think of political decisions as fairer, and are more willing to obey decision outcomes they oppose, if the decision is made by referendum instead of by elected representatives, experts, or judges (Esaiasson et al, 2012;Gash and Murakami, 2015;Towfigh et al, 2016;Esaiasson et al, 2019;Werner and Marien, 2022). At the same time, a unique field experiment conducted in several dozen Indonesian villages suggests that citizens perceived selections of development projects as significantly fairer and were more willing to make personal contributions, such as labor or materials, if projects were chosen in a referendum rather than by elected representatives (Olken, 2010).…”
Section: Introductionmentioning
confidence: 99%